Evaluating the effect of a driver's behaviour on the range of a battery electric vehicle. (September 2015) - Alvarez, Roberto; López, Alberto; De la Torre, Nieves
A battery electric vehicle uses the electric energy stored in a battery to supply power to the electric motor. The estimation of an accurate electric range is an important matter because of the consumer's fear of running out of electricity while driving, often referred to as 'range anxiety'. This article both analyses and quantifies the influence of driving aggressiveness on the battery life. In order to achieve this, a modification of the New European Driving Cycle is performed, simulating progressively more aggressive behaviours. The calculation of the energy consumption and, accordingly, of the vehicle range is performed through a complete vehicle model implemented in MATLAB/Simulink, where an improvement in the battery model is presented, allowing faster processing. The methodology presented can contribute to more efficient management of the power consumed by the vehicle and a decrease in range anxiety.